Quality management of children and youth sports at the municipal level on the basis of monitoring the physical fitness of participants - Chromin, E. V.; Kolunin, E. T.; Cherkasov, V. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a set of measures that improve the quality of management of youth sports at the municipal level based on monitoring data on the physical fitness of those involved.